The development of circ technique leaning management together with flashcards to promote chineese reading of vocational students third year of roi-et technical college - Phuennual , Jatuporn; Wongkamjan, Jitraporn (Journal for Developing the Social and Community, 2022)
The purpose of this research is 1) to compare the ability to read Chinese aloud. Using the CIRC technique learning management in conjunction with flashcards. Of vocational certificate level 3 students at Roi Et Technical College according to criteria 75 2) to compare academic achievement Using the CIRC technique learning management in conjunction with flashcards. Of vocational certificate level 3, Roi Et Technical College The sample group used in this research was 22 students at Vocational Certificate in the Department of Electrician, Semester 2, Academic Year 2020, using the Cluster Random Sampling method. These include: 1) a learning management plan using CIRC technique in conjunction with 6 flashcards, 12 hours; 2) 6 sets of scoring rubrics 3) the achievement measurement form. Learn chinese Four multiple choice tests, 40 questions, statics used for data analysis: percentage, mean, standard deviation, t-test (Dependent Samples). The results of the research were as follows: Students at Vocational Certificate Level 3, Roi Et Technical College Using the CIRC technique learning management in conjunction with flashcards of 22 students, it was found that all students had a score of 75 or higher. Students at Vocational Certificate Level 3, Roi Et Technical College By using the CIRC technique learning management together with flashcards of 22 people, it was found that the average of the post-test scores was higher than the average of the pre-school test scores. Together with flashcards for vocational certificate third year students had higher post-study achievement than before studying, which was statistically significant at the .05 level.